2021
DOI: 10.1007/s11604-021-01118-4
|View full text |Cite|
|
Sign up to set email alerts
|

An analysis of the radiological factors associated with respiratory failure in COVID-19 pneumonia and the CT features among different age categories

Abstract: Purpose To investigate CT patterns of COVID-19 pneumonia associated with respiratory failure (RF) focused on the distribution of lesions. Materials and methods Eighty-five patients with COVID-19 pneumonia were reviewed. CT findings were classified as follows: Type A; patchy ground glass attenuation (GGA) with/without air-space consolidation, Type B; non-segmental GGA with/without air-space consolidation in both the central and peripheral lung portions especially with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The CTs showed subpleural GGOs extending beyond the segmental area, consistent with the radiological characteristics reported in previous studies. These subpleural GGOs appeared in the early to a progressive phase of infection (between day 0 and 8 after symptom onset) [ 10 ] and were a predictor of respiratory failure in patients with COVID-19 [ 14 ]. Furthermore, we also found that in some patients who improved without oxygen therapy, organizing pneumonia (OP)-like consolidation was the dominant pulmonary lesion.…”
Section: Introductionmentioning
confidence: 99%
“…The CTs showed subpleural GGOs extending beyond the segmental area, consistent with the radiological characteristics reported in previous studies. These subpleural GGOs appeared in the early to a progressive phase of infection (between day 0 and 8 after symptom onset) [ 10 ] and were a predictor of respiratory failure in patients with COVID-19 [ 14 ]. Furthermore, we also found that in some patients who improved without oxygen therapy, organizing pneumonia (OP)-like consolidation was the dominant pulmonary lesion.…”
Section: Introductionmentioning
confidence: 99%
“…eases 2019 (COVID- 19), a clinical entity that may cause from pauci-symptomatic illness to severe bilateral interstitial pneumonia, also leading to acute respiratory distress syndrome [1][2][3][4]. Ground glass opacities, consolidation and crazy paving pattern are typical chest computed tomography (CT) findings of COVID-19 [3,[5][6][7][8][9][10][11]. Spontaneous mutations in viral genome, especially when they occur on the receptor binding domain, can be associated with the circulation of viral variant of concern (VOCs), leading to either increased transmissibility, disease severity, or reduction in antibody neutralization and response to vaccines and therapies [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…[44] The frequency of BE in the acute phase of SARS-CoV-2 pneumonia depends on several factors, such as the severity and distribution of the pneumonic process, the need for admission to an intensive care unit, and the days elapsed between the onset of symptoms and the CT scan. [36,37,42] The probability of BE occurrence becomes greater as the number of days increases. Ding et al [36] examined 112 patients with COVID-19 and observed that the prevalence of BE increased as the time between the onset of symptoms and the CT scan increased, from a prevalence of 6.3% when the CT scan was performed 0 to 4 days after the onset of symptoms to 45.2% when the period between the onset of initial symptoms and the CT scan was >28 days.…”
Section: Be and The Acute Phase Of Covid-19 Pneumoniamentioning
confidence: 99%
“…The percentage of patients with BE observed in the early phase of pneumonia is highly variable, according to the studies undertaken (6.3–52.0%) [35–42] . Bao et al [20] performed a systematic review with meta-analysis to provide a more accurate estimate of the detection of COVID-19 by chest computed tomography (CT) and reported the most common findings in imaged chest CT.…”
Section: Be and The Acute Phase Of Covid-19 Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation